2013
DOI: 10.3892/mmr.2013.1717
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin promotes the proliferation of chondrocytes and affects the expression of ADAMTS-5 and TIMP-4 through MEK/ERK signaling

Abstract: The involvement of osteoprotegerin (OPG) in bone metabolism has previously been established; however, whether OPG regulates chondrocytes directly and exerts precise cellular and molecular effects on chondrocytes remains to be determined. Thus, the present study aimed to investigate the direct effect of OPG on the viability, proliferation and functional consequences of chondrocytes. Primary chondrocytes were isolated from the knee of Sprague-Dawley rats. Passage 1 chondrocytes were identified by toluidine blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…the dual-luciferase reporter assay further suggested that TNFRSF11B was a direct target of miR-145 in chondrocytes. TNFRSF11B, as a key regulator of the process of chondrogenesis, has been reported to be important in chondrocyte formation (18)(19)(20). In the present study, the overexpression of miR-145 repressed the expression of TNFRSF11B in C-20/A4 and CH8 cells and, as expected, interference of the expression of TNFRSF11B decreased chondrocyte growth and fibrosis.…”
Section: A B Csupporting
confidence: 85%
“…the dual-luciferase reporter assay further suggested that TNFRSF11B was a direct target of miR-145 in chondrocytes. TNFRSF11B, as a key regulator of the process of chondrogenesis, has been reported to be important in chondrocyte formation (18)(19)(20). In the present study, the overexpression of miR-145 repressed the expression of TNFRSF11B in C-20/A4 and CH8 cells and, as expected, interference of the expression of TNFRSF11B decreased chondrocyte growth and fibrosis.…”
Section: A B Csupporting
confidence: 85%
“…We previously revealed that OPG is able to suppress ADAMTS-5 expression in vitro (Feng et al 2013). In this study, we further demonstrated that the number of ADAMTS-5-positive cells in cartilage is reduced significantly by Ad-OPG treatment in vivo.…”
Section: Discussionsupporting
confidence: 59%
“…We previously found that OPG could inhibit ADAMTS-5 expression in chondrocytes in vitro (Feng et al 2013). In this study, we discovered that the ADAMTS-5-positive cells spreaded all over the full thickness of cartilage with the number increasing significantly in the cartilage of rats treated with a vehicle (Fig.…”
Section: Effect Of Ad-opg On Expression Of Adamts-5 In Cartilagementioning
confidence: 78%
“…The apparent loss of SDC4 could be due to protein destabilization after Hep I pre-treatment or the specific antibody used may require heparan sulphate to completely bind SDC4. Finally, since extracellular signal-regulated kinase 1 and 2 (ERK) phosphorylation was previously documented upon OPG treatment[13, 16], we analysed if Hep I could also block this phosphorylation. As shown in Figure 4G - bottom panels, Hep I pre-treatment were able to block ERK activation.…”
Section: Resultsmentioning
confidence: 99%